Rv2629 Overexpression Delays Mycobacterium smegmatis and Mycobacteria tuberculosis Entry into Log-Phase and Increases Pathogenicity of Mycobacterium smegmatis in Mice - Liu, Dan; Hao, Kewei; Wang, Wenjie; Peng, Chao; Dai, Yue; Jin, Ruiliang; Xu, Wenxi; He, Lei; Wang, Hongyan; Wang, Honghai; Zhang, Lu; Wang, Qingzhong (Frontiers in Microbiology, 2017)
Objective: The aim of the present study was to explore the potential biological role of Rv2629 in Mycobacterium smegmatis and Mycobacterium tuberculosis. Methods: Recombinant wild type and mutant Rv2629 strains were constructed. Rv2629 expression was evaluated by real-time PCR and western blot. Microarray and interaction network analyses were used to identify the gene interactions associated with wild type and mutant Rv2629. Bacterial growth was assessed in Balb/c mice infected with wild type and mutant Rv2629 strains using CFU assay and histological analysis of the organs. Results: Overexpression of Rv2629 could delay the entry of the Mycobacterium tuberculosis cells into the log-phase, while Rv2629 decreased the number of ribosomes and the expression of uridylate kinase in Mycobacterium smegmatis. The Gene Ontology (GO) and pathway analysis indicated that 122 genes correlated with wild type Rv2629, whereas the Rv2629 mutation led to decrease in the ribosome production, oxidative phosphorylation, and virulence in Mycobacterium tuberculosis. Overexpression of Rv2629 slightly enhanced the drug resistance of Mycobacterium smegmatis to antibiotics, and increased its survival and pathogenicity in Balb/c mice. Conclusion: It is suggested that Rv2629 is involved in the survival of the clinical drug-resistant strain via bacterial growth repression and bacterial persistence induction.